Clinical and molecular features of four Brazilian families with multiple endocrine neoplasia type 1 - Miranda, Isabella Santiago de Melo; Valadares, Luciana Pinto; Barra, Gustavo Barcelos; Mesquita, Pedro Góes; de Santana, Lidiana Bandeira; de Castro, Lucas Faria; Rita, Ticiane Henriques Santa; Naves, Luciana Ansaneli (Frontiers in Endocrinology, 2023)
Objective: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant syndrome characterized by its clinical variability and complexity in diagnosis and treatment. We performed both clinical and molecular descriptions of four families with MEN1 in follow-up at a tertiary center in Brasília. Methods: From a preliminary review of around 500 medical records of patients with pituitary neuroendocrine tumor (PitNET) from the database of the Neuroendocrinology Outpatient Clinic of the University Hospital of Brasília, a total of 135 patients met the criteria of at least two affected family members. From this cohort, we have identified 34 families: only four with a phenotype of MEN1 and the other 30 families with the phenotype of Familial Isolated Pituitary Adenomas (FIPA). Eleven patients with clinical diagnosis of MEN1 from these four families were selected. Results: Variants in the MEN1 gene were identified in all families. One individual from each family underwent genetic testing using targeted high-throughput sequencing (HTS). All patients had primary hyperparathyroidism (PHTP) and the second most common manifestation was PitNET. One individual had well-differentiated liposarcoma, which has been previously reported in a single case of MEN1. Three variants previously described in the database and a novel variant in exon 2 have been found. Conclusions: The study allowed the genotypic and phenotypic characterization of families with MEN1 in follow-up at a tertiary center in Brasília.